Genome‐Wide Transcriptional and Functional Analysis of Endoglin Isoforms in the Human Promonocytic Cell Line U937. Issue 4 (April 2015) - Blanco, Francisco J.; Ojeda‐Fernandez, Luisa; Aristorena, Mikel; Gallardo‐Vara, Eunate; Benguria, Alberto; Dopazo, Ana; Langa, Carmen; Botella, Luisa M.; Bernabeu, Carmelo
<x xml:space="preserve">Abstract</x> Endoglin is an auxiliary cell surface receptor for TGF‐β family members. Two different alternatively spliced isoforms, long (L)‐endoglin and short (S)‐endoglin, have been reported. S‐endoglin and L‐endoglin proteins vary from each other in their cytoplasmic tails that contain 14 and 47 amino acids, respectively. A critical role for endoglin in vascular development has primarily been studied in endothelial cells. In addition, endoglin expression is upregulated during monocyte‐to‐macrophage differentiation; however, little is known about its role in this myeloid context. To investigate the function of endoglin in monocytes, stable transfectants expressing the two endoglin isoforms in the promonocytic human cell line U937 were generated. The differential gene expression fingerprinting of these endoglin transfectants using DNA microarrays and further bioinformatics analysis showed a clear alteration in essential biological functions, mainly those related to "Cellular Movement", including cell adhesion and transmigration. Interestingly, these cellular functions are highly dependent on adhesion molecules, including integrins α1 (CD49a, ITGA1 gene), αL (CD11a, ITGAL gene), αM (CD11b, ITGAM gene) and β2 (CD18, ITGB2 gene) and the chemokine receptor CCR2 (CD192, CCR2 gene), which are downregulated in endoglin transfectants. Moreover, activin A (INHBA gene), a TGF‐β superfamily member involved in macrophage polarization, was distinctly affected in each endoglin transfectant, and may contribute to the regulated expression of integrins. These data were confirmed by quantitative PCR, flow cytometry and functional tests. Taken together, these results provide new insight into endoglin function in monocytes. J. Cell. Physiol. 230: 947–958, 2015. © 2014 Wiley Periodicals, Inc.